Effect of Tomato Juice in Tris-Yolk-Citrate Extender on Refrigeration Preservation of Cauda Epididymal Spermatozoa of Buck - Chaudhary, LM; Khasatiya, CT; Amarjeet,; Yede, AB (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was carried out on the preservation of epididymal spermatozoa of buck at refrigerated temperature without and with tomatojuice as a supplement in Tris egg yolk citrate extender. The eight pairs of testicles including epididymis (total 16) from slaughtered buckswere collected within 2–4 hours of their slaughter. Sperms collected from cauda epididymis were preserved at refrigerated temperatureup to 48 hours in tris egg yolk citrate extender at 300 million sperm/mL with different concentration of tomato juice (0%, 4%, 6%,8%, and 10%) and the physical characteristics of spermatozoa were assessed to know the effect of tomato juice (Tj). The mean dead,abnormal and HOST non-reacted spermatozoa increased significantly (p
Keywords: Correlation; , Epididymal spermatozoa; Refrigerated temperature; Refrigerated; Tomato juice